New Zn(II) coordination polymer of indole-3-acetic acid, a plant-growth promoting hormone: Crystal structure, spectroscopic characterization, DFT calculations and microbiological activity. (15th July 2020) - Szmigiel-Bakalarz, Ksenia; Skoczyńska, Anna; Lewańska, Monika; Günther, Daniel; Oeckler, Oliver; Malik-Gajewska, Magdalena; Michalska, Danuta; Morzyk-Ociepa, Barbara
Graphical abstract: Highlights: [Zn(I3AAH)2 )]n (1 ), a 2D polymer of plant hormone (I3AAH2) was synthesized. The structure of 1 was confirmed by XRD, FT-IR, FT-Raman, 1 H and 13 C NMR studies. Zn(II) is bound by four oxygen atoms of four O-deprotonated I3AAH − ligands. For 1, the inhibition zones for bacteria were from 11 mm to 14 mm. Abstract: A new 2D coordination polymer of indole‑3‑acetic acid (I3AAH2) with Zn(II), [Zn(I3AAH)2 ]n (1 ) has been synthesized and fully characterized using single-crystal X-ray diffraction, infrared, Raman, 1 H and 13 C NMR spectroscopy, DFT calculations and microbiological activity tests. The crystal structure is monoclinic, space group P 21 / n, with a  = 6.1948(2), b  = 7.4954(3), c  = 36.2877(12) Å, β  = 94.006(3)°, V = 1680.81(9) Å 3 and Z = 4. The Zn atom is bound to four oxygen atoms of four O-deprotonated I3AAH − ligands, in a slightly distorted tetrahedral environment. The carboxylate groups adopt the μ-O, O′ bidentate bridging mode. Non-classical CH⋯O intra- and intermolecular interactions provide ancillary structural stabilization of 1. A theoretical study was carried out at the B3LYP/6–31++G(d, p) level. Detailed vibrational assignment for 1 was based on the calculated PED. The in vitro antibacterial activity against Gram-negative ( E. coli, P. aeruginosa ) and Gram-positive ( B. subtilis, L. monocytogenes and S. aureus ) bacteria and in vitro antifungal activity against A. niger and C. albicans of 1 were investigated. For comparison, similar microbiological tests were performed for four other Zn(II) complexes (2 –5 ) with indolecarboxylic acids reported earlier. For 1, the inhibition zones for bacteria were from 11 mm to 14 mm, but for fungi, no inhibition zones were observed. Promising results were obtained for 3, against B. subtilis, L. monocytogenes and A. niger and for 4 against B. subtilis (with inhibition zones >20 mm).